Tindak Tutur Direktif Ceramah Ustadzah Haneen Akira dalam Video Sharing Ladies Day pada Kanal Youtube Haneen Akira - Rahma Anggita Purnami; Viyasqi Arsy Putri; Shofia Ambar Muaazaroh; Afia Ananta Izmi; Al Mujahidatul 'Adilah; Asep Purwo Yudi Utomo; Riyadi Widhiyanto (Universitas Palan, 2026)
This study was motivated by the importance of understanding directive speech acts in the context of lectures as a form of effective da’wah communication in contemporary society. The purpose of this study was to identify and analyze the forms and functions of directive speech acts in Ustadzah Haneen Akira's lectures on the YouTube channel Sharing Ladies Day. The research method used is a qualitative descriptive approach with observation and note-taking techniques to collect data from sermon transcripts as the primary data source. The results show that the directive speech acts that appear include the functions of advising, commanding, prohibiting, requesting, and questioning, which are delivered in a gentle, polite, and persuasive style so that they are easily accepted by the audience. In addition, these speech acts reflect the speaker’s intention to influence, guide, and encourage listeners toward positive behavioral changes. This research provides benefits in enriching pragmatic studies, especially in the field of speech act analysis, and serves as a practical reference for preachers in delivering da’wah messages in a more communicative, contextual, and effective manner in the digital era.